Assessment of the Diuretic Effect of the Leaves of Cucumis Dipsaceus Ehrenb (Cucurbitaceae) in Rats: Using Aqueous and 80% Methanol Extracts - Asefa L; Nedi T (Dove Medical Press, 2024)
Lishan Asefa,1 Teshome Nedi2 1Department of Biomedical Science, College of Veterinary Medicine and Agriculture, Addis Ababa University, Bishoftu, Ethiopia; 2Department of Pharmacology and Clinical Pharmacy, College of Health Sciences, Addis Ababa University, Addis Ababa, EthiopiaCorrespondence: Lishan Asefa, Email lishanasefa2005@gmail.com; lishan.asefa@aau.edu.etBackground: The diuretic activity of the Cucumis dipsaceus leaf, which is used in indigenous medicine, has been claimed but has not yet undergone scientific evaluation.Objective: The objective of this study was to assess the diuretic activity of the aqueous and 80% methanol extracts derived from the leaves of Cucumis dipsaceus in rats.Methods: For the extraction process, the maceration technique was employed to obtain the aqueous and 80% methanol extracts from the Cucumis dipsaceus leaves. Male rats were then divided randomly into eight groups, with six rats in each group. These groups consisted of a negative control group, a positive control group, and three different groups for each extract at varying doses. The urine output volumes, the concentrations of urinary electrolytes (sodium, potassium, and chloride) and urinary pH, were measured and analysed to compare the results among the different groups.Results: Both the aqueous and 80% methanol extracts of Cucumis dipsaceus leaves demonstrated a significant increase in urinary output at doses of 200mg/kg body weight (p< 0.01) and 400mg/kg body weight (p< 0.001). When comparing the urinary electrolyte excretion with the negative control group, the groups treated with the 400mg/kg body weight dose of the aqueous extract showed significant differences in the urinary excretion of sodium (p< 0.05), chloride (p< 0.01), and K+ (p< 0.01). Similarly, the urinary excretion of K+ and Cl- also exhibited significant differences at moderate doses (K+: p< 0.01, Cl-: p< 0.05) and the highest doses (both: p< 0.01) of the 80% methanol extract. Furthermore, the highest doses of both the aqueous (p< 0.01) and 80% methanol (p< 0.01) extracts demonstrated significant differences in saluretic effect.Conclusion: Both crude extracts of C. dipsaceus leaves have significant diuretic activity, providing support for the traditional use of the plant as a diuretic agent.Keywords: Cucumis dipsaceus, diuretic activity, electrolyte excretion, Na+/K+ ratio